2021
DOI: 10.1016/j.ajic.2021.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of In-Hospital infection with SARS-CoV-2 among Inpatients at a university hospital

Abstract: Objective The objective of this study was to evaluate the incidence of nosocomial infection and the impact of cross-transmission of SARS-CoV-2 among inpatients at a tertiary care teaching hospital. Methods This was a retrospective cohort study involving inpatients admitted to a tertiary university hospital in the city of São Paulo, Brazil, between March 2020 and February 2021. Cases were identified on the basis of a positive reverse-transcription polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In a mostly unvaccinated population in which most infections were caused by pre-Alpha variant SARS-CoV-2 (6), we found that 7.4% of all COVID-19 patients had probable or definite healthcare-associated COVID-19. This finding is comparable to that from the second wave in Brazil (8.6%) (7) but lower than that from the first wave in the United Kingdom (9%-15%) (2,3). We were able to link only half of the healthcare-associated cases in our hospital to an identified index patient.…”
Section: The Studysupporting
confidence: 62%
“…In a mostly unvaccinated population in which most infections were caused by pre-Alpha variant SARS-CoV-2 (6), we found that 7.4% of all COVID-19 patients had probable or definite healthcare-associated COVID-19. This finding is comparable to that from the second wave in Brazil (8.6%) (7) but lower than that from the first wave in the United Kingdom (9%-15%) (2,3). We were able to link only half of the healthcare-associated cases in our hospital to an identified index patient.…”
Section: The Studysupporting
confidence: 62%
“…Despite two attempts at environmental decontamination in late 2019, FRCP candidemia episodes remained a persistent and increasing challenge in early 2020 [18]. Since the first COVID-19 case in Brazil was reported on 25 February 2020 [19], many preventive measures, such as proper hand hygiene, were reinforced to minimize SARS-CoV-2 contamination in Brazilian hospitals [20]. However, in May 2020, an unexpected increase in the incidence of FRCP candidemia was reported in a Brazilian cardiology referral center, which provides emergency cardiac care for inpatients from the cancer center, suggesting an inter-hospital transmission of FCRP isolates through shared ICU patients.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the proactive and comprehensive infection control response at COH was paramount to preventing the spread of COVID‐19, with no documented nosocomial patient to patient or staff to patient transmission as of September 2021. This is impressive considering that nosocomial transmission of COVID 15–17 and other common respiratory viruses 18,19 has been documented.…”
Section: Discussionmentioning
confidence: 94%
“…patient or staff to patient transmission as of September 2021. This is impressive considering that nosocomial transmission of COVID [15][16][17] and other common respiratory viruses 18,19 has been documented.…”
Section: The Introduction Of the In-housementioning
confidence: 91%